2017
DOI: 10.1097/lbr.0000000000000339
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Transbronchial Needle Aspiration Versus Endobronchial Ultrasound–guided Transbronchial Needle Aspiration, With or Without Rapid On-Site Evaluation, for the Diagnosis of Sarcoidosis: A Randomized Controlled Trial

Abstract: When performing TBNA in the setting of suspected sarcoidosis, we found c-TBNA with ROSE and EBUS-TBNA (with or without ROSE) to be superior to c-TBNA alone. Whether c-TBNA with ROSE is equivalent to EBUS-TBNA cannot be determined from our study due to small sample size/low power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 21 publications
4
62
0
1
Order By: Relevance
“…This technique is of greater significance in situations with benign aetiologies of mediastinal lymphadenopathy (such as TB and sarcoidosis) and lymphoma, which is known to have a lower yield on EBUS . However, when the suspected diagnosis is sarcoidosis, it is preferable to combine trans‐bronchial lung biopsy and endobronchial biopsy with EBUS‐TBNA, which may avert the need to do EBUS‐ TBFB . In our study, EBUS‐ROSE negative but EBUS‐TBFB positive included 6/8 patients with TB, 1/8 with invasive aspergillosis and 1/8 patients with lymphoma.…”
Section: Discussionmentioning
confidence: 86%
“…This technique is of greater significance in situations with benign aetiologies of mediastinal lymphadenopathy (such as TB and sarcoidosis) and lymphoma, which is known to have a lower yield on EBUS . However, when the suspected diagnosis is sarcoidosis, it is preferable to combine trans‐bronchial lung biopsy and endobronchial biopsy with EBUS‐TBNA, which may avert the need to do EBUS‐ TBFB . In our study, EBUS‐ROSE negative but EBUS‐TBFB positive included 6/8 patients with TB, 1/8 with invasive aspergillosis and 1/8 patients with lymphoma.…”
Section: Discussionmentioning
confidence: 86%
“…In the other study, there was no difference in the yield with sampling of either 1 or 2 lymph nodes [13]. Other studies in subjects with sarcoidosis have shown no difference in the yield with either the 21G or 22G needle or with the use of ROSE [8,9]. A small study of 11 subjects showed that the 19G conventional TBNA needle, when used with the EBUS scope, yielded tissue with better preservation of cellular architecture than that obtained with the 22G needle [12].…”
Section: Discussionmentioning
confidence: 97%
“…A few studies have analyzed various technical aspects of the EBUS-TBNA procedure in subjects with sarcoidosis (Table 3) [8,9,[11][12][13]. Two prospective observational studies have shown that the diagnostic yield increases for up to 4 or 5 total passes made [11,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations